LEGAL CERTAINTY OF HALAL CERTIFICATION FOR MSMEs IN THE ISLAMIC ECONOMIC ECOSYSTEM - Lusi Zafriana, Lusi Zafriana (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study is situated within the discourse of Islamic business law, particularly focusing on legal certainty in halal certification for Micro, Small, and Medium Enterprises (MSMEs) within Indonesia’s Islamic economic ecosystem. The issue addressed is that, despite the existence of a strong legal framework governing halal certification, its implementation for MSMEs continues to face challenges related to access, procedural complexity, assistance, and supervision. This study aims to analyze the construction of legal certainty in halal certification for MSMEs and to examine its role in strengthening the position of MSMEs within the Islamic economic ecosystem. The research employs a normative juridical method with statutory and conceptual approaches. Data are collected through a literature review of laws and regulations, official government documents, institutional reports, and relevant scholarly articles; this study does not involve population or sampling as it is non-empirical in nature. The findings indicate that halal certification is structured through mandatory certification, mandatory disclosure for non-halal products, phased implementation for micro enterprises, the self-declare scheme, and free halal certification facilitation programs. However, legal certainty is only meaningful when supported by clear procedures, accessible systems, affordable costs, adequate assistance, and consistent supervision. This study contributes to Islamic business law by positioning halal certification as a legal instrument that enhances consumer protection, market trust, and the sustainability of MSMEs. Halal certification should therefore be understood as an inclusive mechanism for strengthening the Islamic economy, rather than merely an administrative formality.